Challenges for Local Government in the Years 2014-2020 - Słodowa-Hełpa , Małgorzata (Studia Oeconomica Posnaniensia, 2013)
Against the background of the experience of local governments and their activities as regards the absorption of EU funds, this paper presents the main challenges that local governments are likely to face in terms of planning and finance in the years 2014-2020. In particular, the paper focuses on the requirements of the European Commission towards regions; including the need for integrated development management, smart specialization, community-led development and integrated territorial investment.